Tying Dry Flies : HOW TO TIE AND FISH MUST-HAVE TROUT PATTERNS - Nichols, Jay; Craven, Charlie; Weamer, Paul; Heck, Mike (Lanham, MD, United States : STACKPOLE BOOKS, 2021)
"This book of practical fly design is for every tier, from beginner to expert. Tying Dry Flies presents traditional techniques and showcases twenty-six essential patterns--both traditional and innovative new patterns--along with clear and concise instructions and photographs for flies that will work for all kinds of insects in all kinds of situations."--Back cover
Includes index
Keywords: Fly tying; Trout fishing